Análise tecnológica e sócio-econômica do cultivo de moluscos bivalves em sistema familiar na baía da Ilha Grande, Angra dos Reis, RJ - Moschen, Fernando Vitor de Abreu [UNESP] (2007)
Mariculture started as an activity among traditional fishermen families of Ilha Grande bay in 1996 through the Sustainable Development Project. This project, executed by the City council of Angra dos Reis, consisted of the installation of 20 marine farms. The species cultivated were the mussel Perna perna and the scallop Nodipecten nodosus, native species in the region with excellent potential with regards to zoo-technical performance and market-value. This study attempts to describe the state-of-the-art of shellfish culture in the region, through a socioeconomical survey, identifying production technologies of mussels and scallops being used by each producer. With the information and data gathered, it was possible to make an economical analysis of mussel and scallop culture in the region. Three culture configurations were analyzed: System A - composed of 4 long-lines, with production capacity of 3.030 of shell-on mussels and 7.500 units of scallops. System B - composed of 6 long-lines, with production capacity of 4.545 kg of shell-on mussel and 11.250 units of scallop. System C - composed of 18 long-lines with production capacity of 15.150 kg of mussels and 30.000 units of scallops. System A showed to be economically unfeasible after payment of local taxes (ICMS) upon marketed products. Nonetheless, this system showed feasibility if the taxes weren't applied. Systems B and C showed economically feasibility independently of the payment of taxes. The monthly gains varied between R$888,03 and R$3.799,57 according to the system.